German banks' behavior in the low interest rate environment - Ramona Busch; Helge C. N. Littke; Christoph Memmel; Simon Niederauer (Financial Markets and Portfolio Management, 2021)
Using data from a quantitative survey of German banks at three points in time (2015, 2017 and 2019), we analyze the impact of changes in the interest rate level on banks' net interest income and the countermeasures they take. A decline in the interest rate level has a more negative impact on net interest income, the longer the decline lasts and the lower the interest rate level is. This impact softens with increasing risk of changes in the present value of banking books. We do not find that banks generally increase their risks following a drop in income. However, poorly capitalized banks subsequently increase the credit risk of their bond portfolio. After a fall in operational income, banks increase their fee and commission income and reduce their costs. In addition, banks tend to extend their mortgage lending after a drop in their interest income.
Keywords: 330; Banks' net interest margin; Fee and commission income; Low interest rate environment; Risk-taking; Administrative costs; G 21